A radioligand receptor binding assay for ciguatoxin monitoring in environmental samples: Method development and determination of quality control criteria. (December 2018) - Díaz-Asencio, Lisbet; Clausing, Rachel J.; Rañada, Ma Llorina; Alonso-Hernández, Carlos M.; Dechraoui Bottein, Marie-Yasmine
Abstract: Ciguatoxins are algal toxins responsible for tens of thousands of human intoxications yearly, both in tropical and subtropical endemic regions as well as worldwide through fish exportation. Previously developed methods for biotoxin surveillance in the environment and seafood include analytical methods and in vivo and in vitro bioassays. The radioligand receptor binding assay (r-RBA) is among the in vitro methodologies currently used for the detection and quantification of marine biotoxins. For the ciguatoxin group, the r-RBA has been widely used as a means to characterize the mode of action and as detection method in various biological matrices. Yet, screening methods have not been standardized, and the details of the ciguatoxin-specific r-RBA are not well-documented, which limit interlaboratory comparison and progress toward method validation. This work presents the development of an optimized r-RBA for ciguatoxins and provides guidance on its use and quality control checks for analysis of environmental samples. We focus on the analysis of critical parameters involved in determining assay acceptability. Calculation of toxin concentrations in fish samples is illustrated with four examples. Thus, this paper provides the detailed information required for a full validation of the r-RBA, a necessary step toward the development and implementation of a regulatory monitoring programme for ciguatoxins in seafood products using the r-RBA. Highlights: An optimized radioligand-receptor binding assay for ciguatoxins is presented. Critical parameters involved in determining assay acceptability are identified and analyzed. The nuclear based receptor binding assay is a useful tool to support ciguatoxin risk assessment and regulatory action.